Charles Henry Fromuth papers - Fromuth, Charles Henry, 1861-1937.
Diaries, autobiographical manuscripts, exhibition catalogs, newspaper clippings, paint palettes, and other papers relating principally to Fromuth's life and work as an American expatriate artist living in France.
Smithsonian Institution.
Library of Congress Prints and Photographs Division.
Artist.
Collection material in English, with French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Art, American -- France; Artists -- United States; Expatriate artists -- France; Artists